2004
DOI: 10.1111/j.1439-0310.2004.01035.x
|View full text |Cite
|
Sign up to set email alerts
|

Immediate and Delayed Benefits of Play Behaviour: New Evidence from Chimpanzees (Pan troglodytes)

Abstract: Evidence for the anticipation of competition at feeding time has been previously documented in both Pan species. Chimpanzees seem to cope with competitive tendency through behavioural mechanisms of tension reduction, and grooming is certainly one of these. Social play and grooming are often matched because they bring animals into close physical contact for long periods, and they have an important role in social cohesion. Our goal was to investigate the occurrence of play behaviour during the pre-feeding period… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
84
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(86 citation statements)
references
References 33 publications
(78 reference statements)
2
84
0
Order By: Relevance
“…Animals may play to learn valuable social skills (Biben 1998) or to strengthen (Bekoff 1984) or test social bonds (Zahavi 1977;Pozis-Francois et al 2004), as training for cognitive (Bekoff 1984;Spinka et al 2001) or motor development (Byers 1998), to develop the emotional flexibility needed for dealing with unexpected situations (Spinka et al 2001) or as a way to assess their own capabilities relative to conspecifics (Thompson 1998;Smith et al 1999;Palagi et al 2004). Although all of these hypotheses seem reasonable, it is extremely difficult to determine the reproductive benefits of social play.…”
mentioning
confidence: 99%
“…Animals may play to learn valuable social skills (Biben 1998) or to strengthen (Bekoff 1984) or test social bonds (Zahavi 1977;Pozis-Francois et al 2004), as training for cognitive (Bekoff 1984;Spinka et al 2001) or motor development (Byers 1998), to develop the emotional flexibility needed for dealing with unexpected situations (Spinka et al 2001) or as a way to assess their own capabilities relative to conspecifics (Thompson 1998;Smith et al 1999;Palagi et al 2004). Although all of these hypotheses seem reasonable, it is extremely difficult to determine the reproductive benefits of social play.…”
mentioning
confidence: 99%
“…Our study, along with an abundant literature on a variety of primate species (Palagi et al, 2004), suggests that adult social play may be involved in tension reduction and creation of new bonds. But it most often (apart from maybe bonobos and geladas: Palagi et al, 2004) relates to stressful situations, social disturbance or instability (as shown in horses).…”
Section: Adult Play: a Part Of The Behavioral Repertoire?mentioning
confidence: 73%
“…Of course this contradicts the common view that play is suppressed by stress (Palagi et al, 2004) and is indicative of good welfare. Since the early hypotheses of Newberry and Wood-Gush (1988) and others, and in agreement with the statement that play is indicative of "having fun" (Spinka et al,p.…”
mentioning
confidence: 78%
See 1 more Smart Citation
“…Social play in particular may aid in learning the boundaries of social relationships in a safe environment where there are relatively few penalties for transgressions (Bekoff 2001). In chimpanzees, play rates become elevated in captive populations just before feeding time (Palagi et al 2004), and therefore may also function in reducing tension and preventing conflict escalation.…”
Section: Play and The Social Brainmentioning
confidence: 99%